Biofilmes de Trichosporon asahii e Trichosporon inkin: aspectos morfofisiológicos, sensibilidade a antifúngicos e inibição mediada por ritonavir - Serpa, Rosana (2016)
In recent years, several studies have considered Trichosporon genus as emerging opportunistic pathogens in immunocompromised patients. Although the dynamics are not well understood, it is known that events associated with biofilm formation on these fungi play an important role in the infectious process. Thus, the present study analyzed morphophysiological aspects of biofilms produced by Trichosporon spp., as well as the role of a protease inhibitor on T. asahii and T. inkin cells and biofilms. In the first part of the study, we investigated the biofilm formation of T. inkin (n=7) in RPMI broth, CLED broth and Sabouraud broth at pH 5.5 and pH 7.0, with initial inoculum of 1x104, 1x105 and 1x106 cells/ml, incubated at 28°C and 35°C in static or shaking at 80 rpm. Biofilms were evaluated for their biomass and metabolic viability, viable cell counts, quantification of nucleic acids and proteinase activity. It was also investigated the sensitivity of the biofilm front of amphotericin B, caspofungin, fluconazole, itraconazole and voriconazole. To evaluate the inhibitory activity of ritonavir on the structure and functioning of T. asahii and T. inkin biofilms, biofilms were formed in the presence of ritonavir and evaluated for cell adhesion, structural development and proteinase activity. Additionally, ritonavir was assessed on mature biofilms, matrix composition and structural changes. Planktonic cells of T. asahii and T. inkin (n=2 each) were also investigated for sensitivity to ritonavir alone and in combination with antifungals. Finally, planktonic cells were pre-exposed to ritonavir and evaluated for biofilm formation capacity, susceptibility to antifungal agents, and changes in their surface hydrophobicity. Maximum biofilms growth in RPMI pH 7.0 for inoculation of 1x106 cells/ml and incubation at 35°C under stirring. Biofilms produced under these conditions are formed by dynamic communities associated with an extracellular matrix, and show increased viability and biomass over time, reaching stability after 48 hours of cultivation. During the development of biofilms occurs release of viable cells and nucleic acids into the surrounding environment. T. inkin biofilms produce more proteases and tolerate higher concentrations of antifungals that planktonic cells related. Due to the presence of proteases in the development of T. inkin biofilm, it was hypothesized that these enzymes could be considered important targets in controlling biofilms. The results showed that ritonavir decreased cell adhesion and formation of mature biofilms, and reduce protease activity and change the structure of biofilms. Ritonavir did not affect the viability of mature biofilms, but changed the composition of the extracellular matrix of biofilms, which showed different protein spectra compared to the control group. Ritonavir was able to inhibit planktonic growth of T. asahii and T. inkin approximately 50%. However, there was no synergism between ritonavir and tested antifungals. In planktonic cells, pre-exposure to ritonavir significantly reduced values of minimum inhibitory concentration of Amphotericin B in T. asahii and T. inkin, although not change the response to azoles. Preincubation with ritonavir reduced cell adhesion, but not the formation of mature biofilms, in addition to changing the hydrophobicity of the cell surface. The article detailed characteristics of T. inkin biofilms and showed the potential use of a protease inhibitor in controlling these biofilms.